ACP-EU trade and aid co-operation post Lomé IV - McQueen M. ...[et al] (Commonwealth Secretariat LondonGB, 1997)
Looks at aspects such as ACP-EU relations; the export record of the ACP countries and the role of trade preferences; trade cooperation; government and the private sector; private sector development; aid and foreign investment; future prospects for ACP exports to the EU for agricultural and horticultural products covered by the Common Agricultural Policy; and, the banana protocol.